Red blood cell membrane damage by light‐induced thermal gradient under optical trap. Issue 8 (10th May 2018) - Chowdhury, Aniket; Waghmare, Deepak; Dasgupta, Raktim; Majumder, Shovan K.
Abstract : Rapid membrane damage of optically trapped red blood cells (RBCs) was observed at trapping powers ≥280 mW. An excellent agreement between the estimated laser‐induced thermal gradient across trapped cell's membrane and that typically required for membrane electropermeabilization suggests a mechanism involving temperature gradient‐induced electropermeabilization of membrane. Also the rapid collapse of the trapped cell due to membrane rupture was seen to cause shock waves in the surroundings permeabilizing nearby untrapped cells. When the experiments were carried out with RBCs collected from type II diabetic patients, a noticeable change in the damage rate compared to normal RBCs was seen suggesting a novel optical diagnosis method for the disease. Abstract : Rapid membrane damage of optically trapped red blood cells (RBCs) was observed presumably due to temperature gradient‐induced electropermeabilization effect. When RBCs from type II diabetic patients were studied, a noticeable change in the damage rate compared to normal RBCs was seen suggesting a novel optical diagnosis method for the disease.